2021
DOI: 10.3168/jds.2020-19425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mannan-oligosaccharide and Bacillus subtilis supplementation to preweaning Holstein dairy heifers on body weight gain, diarrhea, and shedding of fecal pathogens

Abstract: The objective of this clinical trial was to evaluate the effectiveness of probiotic, prebiotic, and synbiotic supplementation on average daily weight gain (ADG), duration of diarrhea, age at incidence of diarrhea, fecal shedding of Cryptosporidium oocysts, enteric pathogens, and the odds of pneumonia in preweaning dairy heifer calves on a commercial dairy. Feeding prebiotics and probiotics may improve health and production of calves. Hence, healthy Holstein heifer calves (n = 1,801) from a large California dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 46 publications
2
17
0
2
Order By: Relevance
“…have been effectively utilized as probiotic microorganisms for human, poultry, and swine ( Cutting, 2011 ; Luise et al, 2022 ). In ruminants, only a few studies evaluated the effects of such probiotics on performance, rumen fermentation profile, and health of calves ( Sun et al, 2013 ; Deng et al, 2021 ; Lucey et al, 2021 ), beef steers ( Colombo et al, 2021 ), or lactating dairy cows ( Sun et al, 2013 ; Souza et al, 2017 ; Oyebade et al, 2021 ). Even fewer reports in the literature evaluated the combination of different Bacillus spp., such as B. licheniformis and B. subtilis .…”
Section: Discussionmentioning
confidence: 99%
“…have been effectively utilized as probiotic microorganisms for human, poultry, and swine ( Cutting, 2011 ; Luise et al, 2022 ). In ruminants, only a few studies evaluated the effects of such probiotics on performance, rumen fermentation profile, and health of calves ( Sun et al, 2013 ; Deng et al, 2021 ; Lucey et al, 2021 ), beef steers ( Colombo et al, 2021 ), or lactating dairy cows ( Sun et al, 2013 ; Souza et al, 2017 ; Oyebade et al, 2021 ). Even fewer reports in the literature evaluated the combination of different Bacillus spp., such as B. licheniformis and B. subtilis .…”
Section: Discussionmentioning
confidence: 99%
“…Mammeri et al identified the anti-cryptosporidial activities of chitosan, a natural polysaccharide present in YCW in in vitro and mouse studies [ 28 ]. In another study, yeast culture enriched with mannan-oligosaccharides were fed in milk to Holstein heifer calves enrolled at 4 to 12 h of age, and this led to the presence of fewer Escherichia coli and pathogenic E. coli compared with control calves [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of probiotics against the enteric pathogens suggests their utility as an effective biotherapeutic to prevent related gastrointestinal infections ( Prabhurajeshwar and Chandrakanth, 2019 ). Specifically these native probiotics support the intestinal epithelial barrier by enhancing the expression of barrier function components ( Rokana et al, 2016 ; Bron et al, 2017 ) and prevent the enteric infections in the host ( Lucey et al, 2021 ). Many of the known Lactobacillus probiotic strains produce metabolites, such as diacetyl, acetoin, hydrogen peroxide, and bacteriocins, which prevent the growth of pathogens and assist in defence mechanisms that are involved keeping infections at bay ( Osuntoki and Korie, 2010 ; Pyar and Peh, 2014 ).…”
Section: Impact Of Probiotic Microorganisms On Animals’ Welfarementioning
confidence: 99%